Experimental quantification of vertical stresses during gravity flow in block caving. (March 2020) - Castro, Raúl; Gómez, René; Pierce, Matthew; Canales, Juan
Abstract: Usually in block and panel caving mines, when the caving connects to the surface, monitoring of vertical stresses over production drifts is minimal due to the low probability of seismic events. However, when the stresses over the production level are related to an overburden by fragmented rock, the draw policies highly influence induced stress. In this context, we present an experimental set up using a laboratory-scale model to identify the role of draw strategy on induced vertical stresses in a block-caving layout. Here, three draw strategies are studied: isolated draw, panel caving draw, and block caving draw. Results show that induced vertical stresses can vary between 0.3 and 2.8 times their initial vertical value and are highly influenced by both the distance from the extraction front and the dimension of draw and non-draw areas. These findings provide useful information to support the system design in block caving or panel caving methods to decrease induced vertical stresses related to draw and define rules of extraction in an effort to avoid problems related to the maximum stress that can be expected on production-level pillars .